Patient preferences for topical treatment of AK. (1st April 2019) - Kopasker, D.; Kwiatkowski, A.; Matin, R.N.; Harwood, C.A.; Ismail, F.; Lear, J.T.; Thomson, J.; Hasan, Z.; Wali, G.N.; Milligan, A.; Crawford, L.; Ahmed, I.; et al.
Summary: Actinic keratoses are rough patches of skin caused by years of sun damage. There is a small risk that AK patches could progress into a form of skin cancer called cutaneous Squamous Cell Carcinoma (cSCC). Treatment of AK might therefore provide an effective strategy for cSCC prevention, although this theory has not been rigorously tested. Also, the patient perspective on potential benefits of AK treatment in terms of skin cancer reduction has received little attention to date. Treatments for AK include freezing with liquid nitrogen (cryotherapy), surgical removal, topical treatments such as creams or gels (5‐fluorouracil, imiquimod, ingenol mebutate gel, diclofenac and retinoic acid), photodynamic (light) therapy, or laser treatment. The aims of this study were (i) to investigate patient preferences for topical treatments for AK using a discrete‐choice experiment (DCE); (ii) to evaluate patient willingness to trade between clinical benefit (i.e. how well it works) and medical burden (e.g. inconvenience and unwanted side effects). 109 patients were presented with a series of choices between two hypothetical topical treatments for AK, and a 'no treatment' opt‐out option in each choice set. Different attributes of the hypothetical treatments related to the burden of medication, (intensity and length of treatment, severity of local skin reaction, and occurrence of flu‐like side effects) and the efficacy of treatment (improvement in skin appearance and reduction in skin cancer risk). The analysis of the data is complex, but showed that most patients would be prepared to accept a lower reduction in skin cancer risk (e.g. a 50% reduction in the risk of skin cancer as opposed to a 60% reduction in the risk) and reduced efficacy of treatment (e.g. 50% clearance of AK lesions as opposed to 100% clearance) in order to reduce the length and intensity of the regimen, and side effects including skin inflammation and pain. This highlights the importance for doctors of taking individual patient preferences into account, to improve their views of their AK treatment and the likelihood that they will stick with their treatment.